(untitled) (L’architettura delle città - The Journal of the Scientific Society Ludovico Quaroni, 2018)
The Bay of Durban was discovered in 1497. The city – founded in the cove – was in a strategic position for trades. However, the municipality did not taste an intense development until the nineteenth century when it was annexed to the United Kingdom. In fact, included in an international trade system, the port suffered an economic progress which rapidly transformed the port in the principal center of the region. The opportunity drew the attention of many workers from all over the neighboring provinces, who moved to Durban looking for a job opportunity. This presence of different communities and cultures fashioned both local life and architecture. The rural houses maintained a connection with Dutch heritage tradition of first colonists, as well as a more formal and monumental style had been imported during British domination in order to characterize the government buildings. In this respect, the new City Hall – built in the early 1900’s – with its neo-Baroque-style provided the most stable link to European cultural, developing the model of Belfast’s City Hall in Ireland at that time under construction.